State of Massachusetts-Bay. In the House of Representatives, January 25, 1777 : the perseverance of Britain in her attempts to subjugate the free states of America ... demands a vigorous perseverance in the inhabitants of these states ... For this end the supreme council of the continent ... have called for eighty-eight battalions ... and for fifteen of them from the Massachusetts-Bay . - Freeman, Samuel, 1743-1831; Avery, John, 1739-1806 ([Printed by Benjamin Edes], 1777)
January 26, 1777 Resolutions regarding filling the ranks of the army state militia with those sixteen and over, with some exceptions.